2017
DOI: 10.1038/cmi.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

CD24 aggravates acute liver injury in autoimmune hepatitis by promoting IFN-γ production by CD4+ T cells

Abstract: The T-cell-mediated immune response is implicated in many clinical hepatic injuries, such as autoimmune hepatitis and acute virus hepatitis. CD24 is widely expressed by different immune cells and plays an important role in the pathogenesis of many autoimmune diseases. However, the role of CD24 in T-cell-mediated liver injury has not been elucidated until now. Here we showed that CD24 deficiency protects mice from concanavalin A (ConA)-induced fulminant liver injury by reducing serum interferon-γ (IFN-γ) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…It has been demonstrated that TNF-α, 28 IL-1β, 29 IL-6, 30 COX-2, 31 and HDGF itself 19 were involved in neutrophils infiltration and migration, and these pro-inflammatory mediators also participates in ConAinduced hepatitis. [8][9][10][11] In this research, HDGF ablation or neutralization attenuated ConA-induced the upregulation of TNF-α, IL-1β, IL-6, and COX-2 in the mouse livers and hepatocytes, respectively. Moreover, rHDGF treatment could directly regulate pro-inflammatory signaling in cultured hepatocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…It has been demonstrated that TNF-α, 28 IL-1β, 29 IL-6, 30 COX-2, 31 and HDGF itself 19 were involved in neutrophils infiltration and migration, and these pro-inflammatory mediators also participates in ConAinduced hepatitis. [8][9][10][11] In this research, HDGF ablation or neutralization attenuated ConA-induced the upregulation of TNF-α, IL-1β, IL-6, and COX-2 in the mouse livers and hepatocytes, respectively. Moreover, rHDGF treatment could directly regulate pro-inflammatory signaling in cultured hepatocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 72%
“…The animal model of ConA-induced hepatitis was performed as previously described. 9 Briefly, C57BL/6 mice (male; 6 week old) were used in this study. WT mice were purchased from BioLASCO Taiwan Co., Ltd., and HDGF-KO mice were acquired from Dr Franken group.…”
Section: Cona-induced Hepatitis Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it should be noted that CD24 is also known as a costimulatory molecule for the activation of T cells, 11 including autoreactive T cells, 12 and intrahepatic CD4 T cells. 13 Correspondingly, CD24Fc was also shown to inhibit autoimmune diseases. 14 Because CD24Fc phenocopies the genetic defect of the Cd24 gene in autoimmune diseases, 12,14 it likely works through a different mechanism as an antagonist.…”
mentioning
confidence: 99%